Calculus with Applications (10th Edition)

Published by Pearson
ISBN 10: 0321749006
ISBN 13: 978-0-32174-900-0

Chapter R - Algebra Reference - R.3 Rational Expressions - R.3 Exercises - Page R-11: 29


$\dfrac{1}{m-1}+\dfrac{2}{m}=\dfrac{3m-2}{m(m-1)}$ or $\dfrac{1}{m-1}+\dfrac{2}{m}=\dfrac{3m-2}{m^{2}-m}$

Work Step by Step

$\dfrac{1}{m-1}+\dfrac{2}{m}$ Evaluate the sum of these two fractions by using the LCD, which is $m(m-1)$ in this case: $\dfrac{1}{m-1}+\dfrac{2}{m}=\dfrac{m+2(m-1)}{m(m-1)}=...$ Simplify: $...=\dfrac{m+2m-2}{m(m-1)}=\dfrac{3m-2}{m(m-1)}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.